Potencial antimicrobiano e antibiofilme do extrato hidroalcoólico da casca do caule de Croton blanchetianus - Alves, Mayara Freire de Alencar (2020)
Health care-associated infections (HAIs) have an impact on hospital mortality, length of hospital stay and additional costs that burden the health system. Biofilms are responsible for the pathogenesis of HAIs mainly because they have the facility to adhere to a surface producing an extracellular matrix that facilitates microorganism-microorganism communication, increasing its resistance to antimicrobials. Knowing that extracts from Caatinga plants rich in diterpenes are popularly used as antimicrobials, this study investigated the antimicrobial and antibiofilm activity of the extract isolated from the bark of Croton blanchetianus. In the study, CIM, CMB, metabolic activity, death kinetics of Staphylococcus aureus, Pseudomonas aeruginosa and Candida albicans strains were isolated and combined. Morphological changes were also analyzed using scanning electron microscopy and bacterial cell viability by laser confocal microscopy combined with LIVE / DEAD. To prove that hardwickic acid has no toxicity to eukaryotic cells, keratinocyte and fibroblast cells were tested. Our results suggest that the extract rich in clerodane diterpene, hardwickic acid interferes with planktonic and mono and multispecies biofilm growth by interaction with the microbial membrane and with structures present in the extracellular matrix. This fact reinforces the idea that diterpenes are promising antimicrobials and that the result is of paramount importance for the prospect of a new antimicrobial molecule.